Enrolments in higher education in West Germany: the impact of social background, labour market returns and educational funding - Charlotte Lauer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
This paper analyses the determinants of participation in higher education in West Germany. In particular, the role of social origin as well as of expectations regarding the labour market outcome of a higher education degree and of public educational policy are examined. The estimations are based on a model of utility maximisation, where the decision to enrol in one of several educational tracks of different levels is determined by the expected ratio of marginal cost to marginal return for the different enrolment alternatives given some observed characteristics. The model is estimated empirically on the basis of GSOEP and regional data. The results show that the probability of enrolment in higher education is mainly influenced by social origin. Parental education and occupational position, in particular, are essential. However, the enrolment probability also depends on labour market return expectations. In particular, the absolute level of the personal unemployment risk, rather than the reduction of the unemployment risk to be expected from higher education, is a strong incentive to pursue higher education. The expected return to education in terms of wages also affects educational decisions significantly. A higher propensity to be out of work or employed part-time proved to go along with a lower probability of being enrolled in higher education significantly. Also public policy is found to have an influence on enrolments. In particular, extending the coverage of public financial support in the form of BAföG seems to be more efficient in increasing enrolments than increasing the amount of BAföG granted. The extent of the repayable part of the financial aid has a dampening, though limited, influence on enrolments.
Keywords: I28; I21; 330; educational decisions; costs of education; returns to education; Studium; Bildungsverhalten; Bildungsökonomik; Soziale Schicht; Kosten-Nutzen-Analyse; Bildungsertrag; Bildungspolitik; Schätzung; Deutschland